FUND LOAN PAYMENT SYSTEM P2KP IN SUB WEST KUNINGAN - Agus Riyanto; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2003)
In this paper the author explores the heading "Payment Systems in The Village Fund Loan P2KP West Brass." Principal of the matters to be discussed is a loan payment in installments that in computerization. In this writing consists of understanding the system, data flow diagram which consists of the concept of ERD, and the concept of normalization. Then the design of systems composed of context diagram, diagram of zero, entity relationship diagrams, ERD transformation into relational databases and normalization. Payment systems used to accelerate the authors point out the payment process and delivery of reports in order to create efficiencies and save time working UPK (Financial Management Unit).